PEMANFAATAN MEDIA GAMBAR DALAM MENINGKATKAN PEMAHAMAN MEMBACA SISWA DI SEKOLAH DASAR - Halimatus Sa'diah; Irma Noor Afiyanti; Nadia Febrianti; Ririn Septiawati; Ahmad Suriansyah; Wahdah Refia Rafianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading ability, or literacy, is a competency that students must master from elementary school because it can influence the learning process at the next level. However, some students still experience obstacles in reading due to a lack of interest in reading. The use of visual media is one way that can be used to help students, because it can provide interesting visual images and facilitate understanding of the content of the reading. In the literature review, the use of visual media in improving students' reading comprehension was carried out to identify fundamental concepts, learning strategies, and previous research results to demonstrate the effectiveness of using visual media in students' reading comprehension in elementary schools.